Behavioural and psychiatric symptoms in people with dementia admitted to the acute hospital: prospective cohort study. (September 2014) - Sampson, Elizabeth L.; White, Nicola; Leurent, Baptiste; Scott, Sharon; Lord, Kathryn; Round, Jeff; Jones, Louise
Abstract : Background: Dementia is common in older people admitted to acute hospitals. There are concerns about the quality of care they receive. Behavioural and psychiatric symptoms of dementia (BPSD) seem to be particularly challenging for hospital staff. Aims: To define the prevalence of BPSD and explore their clinical associations. Method: Longitudinal cohort study of 230 people with dementia, aged over 70, admitted to hospital for acute medical illness, and assessed for BPSD at admission and every 4 (±1) days until discharge. Other measures included length of stay, care quality indicators, adverse events and mortality. Results: Participants were very impaired; 46% at Functional Assessment Staging Scale (FAST) stage 6d or above (doubly incontinent), 75% had BPSD, and 43% had some BPSD that were moderately/severely troubling to staff. Most common were aggression (57%), activity disturbance (44%), sleep disturbance (42%) and anxiety (35%). Conclusions: We found that BPSD are very common in older people admitted to an acute hospital. Patients and staff would benefit from more specialist psychiatric support.